Analysis of Coconut Oil Agro-Industry Development Strategy in Kancinaa Village, Pasarwajo District, Buton Regency - Wa Rini; Bahari, Bahari; Rosmawaty, Rosmawaty (International journal of technology and education research, 2024)
This research aims to (1) determine the internal and external factors in developing the coconut oil agro-industry in Kancinaa Village, Pasarwajo District, Buton Regency, (2) determine the strategies that can be implemented in developing the coconut oil agro-industry in Kancinaa Village, Pasarwajo District, Buton Regency. This research was carried out in Kancinaa Village, Pasarwajo District, Buton Regency from January to June 2024. Information was collected through interviews with 12 respondents. The data analysis used in this research is descriptive qualitative. The results of the research show that: that internal factors have a positive influence on people who process coconuts into coconut oil. And external factors show that in general external factors have a quite good influence on the business of developing the coconut oil agro-industry